Providing Value to New Health Technology: The Early Contribution of Entrepreneurs, Investors, and Regulatory Agencies - Lehoux, Pascale (Int J Health Policy Manag, 2017)
Background: New technologies constitute an important cost-driver in healthcare, but the dynamics that lead to their emergence remains poorly understood from a health policy standpoint. The goal of this paper is to clarify how entrepreneurs, investors, and regulatory agencies influence the value of emerging health technologies. Methods: Our 5-year qualitative research program examined the processes through which new health technologies were envisioned, financed, developed and commercialized by entrepreneurial clinical teams operating in Quebec’s (Canada) publicly funded healthcare system. Results: Entrepreneurs have a direct influence over a new technology’s value proposition, but investors actively transform this value. Investors support a technology that can find a market, no matter its intrinsic value for clinical practice or healthcare systems. Regulatory agencies reinforce the "double" value of a new technology—as a health intervention and as an economic commodity—and provide economic worth to the venture that is bringing the technology to market. Conclusion: Policy-oriented initiatives such as early health technology assessment (HTA) and coverage with evidence may provide technology developers with useful input regarding the decisions they make at an early stage. But to foster technologies that bring more value to healthcare systems, policy-makers must actively support the consideration of health policy issues in innovation policy.